The Difference In Menstrual Pain (Dysmenorrhea) Levels Before And After Pineapple (Ananas Comosus L.) Consumption In Early Adolescents At MTS Muhammadiyah 09 Purbalingga - Mutiarani Nur Filanti; Ima Syamrotul Muflihah (Health Science UDINUS, 2024)
Adolescence is a transitional phase, and during this period, young girls experience menstruation. Menstruation is often accompanied by menstrual pain (dysmenorrhea), which is characterized by lower abdominal pain that can radiate to the lower back and thighs. The World Health Organization (WHO) reported in 2018, as cited by Ariyanti et al. (2020), that dysmenorrhea affects more than 50% of women in each country worldwide. In Indonesia, the prevalence of dysmenorrhea is 64.25%, comprising primary dysmenorrhea at 54.89% and secondary dysmenorrhea at 9.36%. According to the Central Java Health Department's profile data, there are 2,899,120 female adolescents aged 10 to 19 years, and 1,465,876 of them experience dysmenorrhea. Pineapple (Ananas Comosus L.) is one of the non- pharmacological therapies used to alleviate menstrual pain. Objective: To analyze the difference in menstrual pain (dysmenorrhea) levels before and after consuming pineapple (Ananas Comosus L.) among early adolescents at MTs (Islamic Junior High School) Muhammadiyah 09 Purbalingga. Method: Pre- Experiment using a one-group pretest-posttest research design. The purposive Sampling Technique was used to select 50 respondents. The research instruments included a questionnaire and the Numeric Rating Scale (NRS). Results: Respondents were in the early adolescent phase (11-14 years). The level of menstrual pain before consuming pineapple showed that a majority experienced mild menstrual pain, with 27 respondents (54%), while after consuming pineapple, a majority reported being pain-free, with 37 respondents (74%). The paired t-test analysis resulted in a P value of 0.001, indicating a significance level of 0.05, which means that H1 is accepted, signifying a difference in menstrual pain levels before and after pineapple consumption among early adolescents at the school